Microplastic Contamination of Rainwater on the Highway with Different Elevations in Yogyakarta Province Indonesia - Gunawan, Almaida Khansa; Utami, Inggita; Andini, Maydiana Ayu; Zahra, Safa Auli (Journal of Biotechnology and Natural Science, 2023)
Abrasion of vehicle tires produced on highways on the imaginary line of Yogyakarta from Bantul up to Sleman Regency with different elevations has the potential to be a source of microplastics in the air and can contaminate rainwater. This study aims to determine the abundance and characteristics of microplastics in rainwater that falls on highways with different elevations in Yogyakarta Province. The study began with determining the sampling point and taking rainwater samples on the highway around Bantul Market, Tugu Monument, and Kaliurang km 14. Eight samples on different days were taken at each sampling point, as much as 250 mL/sample. Rainwater samples were filtered, microplastic abundance was calculated (particles/L), and grouped based on the shape, color, size, and polymer type. The content of microplastics on highways at different elevations in Yogyakarta Province was not significantly different, with an abundance range ranging from 200 to 484 particles/L. Vehicle density, light intensity, air temperature, and wind speed correlated with the abundance of microplastics in rainwater. The dominant characteristic is black fiber, 101-500 µm, and polyisoprene. Microplastics in rainwater that fell on the highways of Yogyakarta Province with varying elevations did not have different abundances but had the same characteristics.